Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae) - Santos-Silva, Antonio; Botero, Juan Pablo; Taboada-Verona, Carlos (Zootaxa, 2017)
Currently, Psyrassa Pascoe, 1866 includes 37 species distributed mainly in southern United States to Central America (Monné 2016; Tavakilian and Chevillotte 2016). Only four species occur in northern South America: P. meridionalis Martins, 2005 (Ecuador); P. rufescens Nonfried, 1894 (Brazil); P. testacea Linsley, 1935 (Colombia, Venezuela, French Guiana); and P. subglabra Linsley, 1935 (Ecuador).